Language and truth: playing with Rubem Alves’ and Jürgen Habermas’ glass beads: contributions to theology - Reblin, Iuri Andréas (2010)
The text establishes a dialogue between Rubem Alves’ thought and Jürgen Habermas’ thought about the function of Language since two specific works: Sigh of the Oppressed and The Theory of Communicative Action. According to Rubem Alves, language is pragmatic. However, even if the words have the primary role of representing things and their relations, the language itself is not a copy of reality, but rather its organization according to human needs. According to Habermas, there is no meaning outside of human action and it is the language that coordinates the actions of different subjects in the same society. Before this, the text demonstrates that theology will only be able to rediscover its place in the world if it learns to deal with the dialectic between language and reality.